Application of Practicum-Based Inquiry Learning Model to Activities and Learning Outcomes of Alsintan Subject Students at SMKN in Takalar Regency - Muhammad Hasan Patahuddin; Lahming; Ervi Novitasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a quasi-experimental research and aims to determine the effectiveness of applying the inquiry learning paradigm to the activities and learning outcomes of students of class X ATP SMKN 6 Takalar. In this study the independent variable is the application of the inquiry learning paradigm, while the dependent variable is student learning activities and outcomes. The population of this study were all ATP students, while the sample consisted of 22 ATP class X students. Based on the findings of this study, the application of a practicum-based inquiry learning model can increase student activity and learning outcomes. study agricultural equipment and machinery. Using the T test to assess the hypothesis in this study, tcount = 16,661 was found to be greater than ttable = 2,974. The application of the practicum-based inquiry learning model has a considerable impact on engagement and student learning outcomes, it can be concluded.